2011
DOI: 10.1111/j.1467-9442.2011.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Corporate Tax Rates Down? A Reassessment of Globalization, Tax Competition, and Dynamic Adjustment to Shocks*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 25 publications
7
67
1
5
Order By: Relevance
“…This is tax competition in its most strategic sense and controlling for such effects might mitigate previously discussed effects on statutory tax rates, yet little research has been done on it. Examples include Devereux et al (2008) and Overesch and Rincke (2011). Both studies found significant evidence for strategic interactions to be pushing down corporate income tax rates.…”
Section: Marblementioning
confidence: 99%
See 4 more Smart Citations
“…This is tax competition in its most strategic sense and controlling for such effects might mitigate previously discussed effects on statutory tax rates, yet little research has been done on it. Examples include Devereux et al (2008) and Overesch and Rincke (2011). Both studies found significant evidence for strategic interactions to be pushing down corporate income tax rates.…”
Section: Marblementioning
confidence: 99%
“…This is the exact same weight function is that of Overesch and Rincke (2011), except for the fact that in this function the proxy for size is GDP (in billions) instead of population. The reasoning behind this is that countries will be more attentive of other countries if they boast more economic power.…”
Section: Strategic Interaction Variablementioning
confidence: 99%
See 3 more Smart Citations